Peran protektif bromelain dan flavonoid dalam kulit nanas terhadap kerusakan sel kulit akibat paparan sinar UV: Sebuah tinjauan sistematis. - Ni Putu Mirah Ayunda Kartika Wulandari; Ni Made Linawati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Exposure to ultraviolet (UV) radiation is a significant cause of skin cell damage through DNA damage, oxidative stress, and the activation of inflammatory pathways. Skin protection generally relies on sunscreens, but increasing interest in natural agents has driven the exploration of bioactive compounds derived from agricultural waste such as pineapple (Ananas comosus) peel. Pineapple peel contains flavonoids and bromelain with antioxidant, anti-inflammatory, and photoprotective potential. This systematic review aims to assess the scientific evidence regarding the protective role of these compounds against UV-induced skin damage. A literature search was conducted using PubMed, ScienceDirect, ProQuest, and Google Scholar in accordance with PRISMA guidelines. The inclusion criteria were in vitro, in vivo, and formulation studies evaluating the effects of pineapple peel extracts on skin damage parameters, including oxidative stress, cytokine modulation, antioxidant enzymes, and sun protection factor (SPF). Eight studies met the criteria. The results showed that formulations containing pineapple peel extract, such as creams, gels, lotions, or biocomposites demonstrated SPF ranging from low to ultra levels of protection. Flavonoids play a role in scavenging free radicals, reducing reactive oxygen species (ROS), and modulating anti-inflammatory effects. Bromelain supports the viability of UV-exposed fibroblasts and enhances the effectiveness of synthetic sunscreens such as octyl methoxycinnamate. Pineapple peel shows strong potential as a source of natural active ingredients for photoprotection through the activity of flavonoids and bromelain. However, further research with standardized designs and clinical trials is needed before it can be applied in sustainable cosmetic and therapeutic formulations.